Revision of the Belostoma dentatum group sensu Nieser (Insecta, Heteroptera, Belostomatidae) - Ribeiro, José Ricardo Inacio; Estévez, Ana Lia; Moreira, Felipe Ferraz Figueiredo; Guilbert, Eric (Zootaxa, 2017)
Species of Belostoma in the dentatum and subspinosum groups are large and closely related, and have been combined by some authors into a single group, the dentatum group, comprising 15 species. This group is recognized by the scutellum reaching the nodal line and the ventral diverticulum of the phallus with distinct dorsal caudal and ventroapical protuberances. Previously, each group included five and 10 species, respectively; members of the dentatum group ranged in length from 38.0 to 52.0 mm, whereas those of the subspinosum group ranged from 26.0 to 40.0 mm. The following species of the dentatum group, now reformulated, include: Belostoma anurum (Herrich-Schäffer), B. asiaticum (Mayr), B. bordoni De Carlo, B. cummingsi De Carlo, B. columbiae Lauck, B. dallasi De Carlo, B. dentatum (Mayr), B. elongatum Montandon, B. ellipticum Latreille, B. foveolatum (Mayr), B. guianae Lauck, B. harrisi Lauck, B. malkini Lauck, B. porteri De Carlo, B. pseudoguianae Roback & Nieser, B. subspinosum Palisot de Beauvois, and B. venezuelae Lauck. Belostoma bordoni is herein included in the dentatum group based on male genitalic morphology, and the subspecies B. subspinosum subpinosum (Palisot de Beauvois) and B. subspinosum cupreomicans (Stål) are synonymized as a single valid species, B. subspinosum. Belostoma peruvianum De Carlo is synonymized with B. dentatum. Based on the study of male genitalic characteristics, B. cachoeirinhensis Lanzer-de-Souza appears to be conspecific with B. cummingsi; however, because we could not borrow types of B. cachoeirinhensis, we do not synonymize it. Sketches of specimens identified either as B. boscii (Le Peletier de Saint-Fargeau & Serville) or B. anurum by A.L. Montandon from Muséum National d’Histoire Naturelle are provided with comments in order to show the variation of male genitalia through the B. subspinosum complex. Our findings suggest that the dorsal arms of the phallotheca curved apically to be diagnostic of this complex. No firm conclusion is possible because of the great variation in the male genitalia; however, the general aspect of the ventroapical protuberance together with the dorsal arms provide some definition of B. subspinosum. A key to these species is also given, deeply modified after D.R. Lauck and N. Nieser.